Draft Five Year Plan 1978-83 School Education Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
In pursuance of the Directive Principle of State Policy to provide free and compulsory education upto the age of 14, the State Government has sought to provide a big net work of educational facilities throughout the State by way of opening large number of educational institutions from year to year. This has resulted into bringing the 62.66% of the children of age group 6-11 and 28.24% of the children of age group 11-14 into school by the date 30.9.77. This indicates that the target of universalisation of elementary education is still a distant goal in the State of Madhya Pradesh.
Government of Madhya Pradesh, Planning, Economics and Statistics Department